Analisis Hubungan antara Kepuasan Kerja, Loyalitas Karyawan, dan Kesejahteraan Finansial Terhadap Produktivitas Kerja dengan Motivasi Kerja Sebagai Variabel Intervening di Sekretariat Daerah Kota Sungai Penuh - Valani, Silvia; Yulasmi, Yulasmi; Veri, Jhon (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to examine the extent of the relationship between job satisfaction, employee loyalty, and financial well-being on work productivity with work motivation as an intervening variable at the Regional Secretariat of Sungai Penuh City. The data collection method was through surveys and distributing questionnaires, with a sample of 82 respondents. The analysis method used was structural equation modeling using SmartPLS. The research results showed a significant influence of job satisfaction on work motivation at the Regional Secretariat of Sungai Penuh City. There is a significant influence of employee loyalty on work motivation at the Regional Secretariat of Sungai Penuh City. There is no significant influence of financial well-being on work motivation. There is no significant influence of job satisfaction on work productivity. There is no significant influence of employee loyalty on work productivity. There is no significant influence of financial well-being on work productivity. There is a significant influence of work motivation on work productivity. Work motivation mediates the influence of job satisfaction on work productivity. Work motivation mediates the influence of employee loyalty on work productivity. Work motivation does not mediate the influence of financial well-being on work productivity